Evaluation of a Community-Based Diabetes Prevention Program in Thailand: A Cluster Randomized Controlled Trial - Wichai Aekplakorn; Valla Tantayotai; Sakawduan Numsangkul; Nutchanat Tatsato; Pranee Luckanajantachote; Thep Himathongkam (SAGE Publishing, 2019)
Objectives: Lifestyle interventions have been shown to effectively reduce the incidence of diabetes, but evidence from middle-income countries is scarce. We evaluated the effectiveness of a lifestyle program to prevent diabetes in primary-care settings in Thailand. Methods: A matched-pair cluster randomized controlled trial was conducted in 68 primary care units in 8 provinces. The primary care units were randomly assigned to intervention or control arms. Individuals aged 30 to 65 years with impaired oral glucose tolerance were recruited and followed up for 2 years. The intervention included periodic group-based activities on healthy lifestyle behaviors; the control group received a one-time education program. The primary outcome was the incidence rate of type 2 diabetes at 24 months after the intervention. Results: A total of 1903 individuals participated (873 in the control group and 1030 in the intervention group). At baseline, participants' characteristics did not differ between groups. After 24 months, the incidence rates (per 100 person-year) of diabetes was 12.1% (95% CI 10.7% to 13.8%) in the intervention group, and 16.6% (95% CI 14.6 to 18.8%) in the control group ( P < .001). Overall, the adjusted hazard ratio for diabetes incidence was 0.72 (95% CI 0.60 to 0.86). A mean body weight reduction of 1.5 kg was observed in the intervention group, whereas, an increase of 0.4 kg was observed in the control group ( P < .001). Conclusion: A community-based lifestyle modification through participatory group activities can prevent or delay the incidence of diabetes among Thai populations with impaired glucose tolerance.